Analisis Kemampuan Berpikir Kritis Pada Materi Hukum Newton Siswa SMA - Singgih Baktiarso; I Ketut Mahardika; Ainiyatun Nadhifah; Anindia Putri; Mufidatus Solehah; Verina Dwisari (Jurnal Ilmiah Wahana Pendidikan, 2023)
Critical thinking skills are students' cognitive processes in which they systematically and accurately analyze the problems they face, carefully and thoroughly differentiate these problems, and identify and analyze information to develop problem-solving strategies. The purpose of this research is to describe the critical thinking of high school students in Newton's law material. However, the results obtained reflect the thinking skills of Indonesian students from top to bottom. From the results of this study, it was concluded that students' weak high-level reasoning abilities indicated that many students made mistakes when solving routine problems in familiar contexts. Data was collected in the form of a multiple choice test in which there were 5 questions provided. The technique used in analyzing the data is to observe students answering questions. From the tests that have been carried out, the results are obtained in terms of the percentage of students' understanding, namely 15% have a good level of understanding, 65% have a fairly good understanding, and 25% have a bad understanding. The conclusion is the ability to think critically and understand physics concepts which are part of Newton's Laws. Students have not been able to think critically on Newton's law questions, namely on calculation questions. Meanwhile, students can still work on questions regarding the concepts of Newton's law.